PREVALENSI PERUBAHAN PERILAKU ANJING LOKAL (Canis familiaris) JANTAN YANG DIKANDANGKAN DENGAN PRINSIP KESEJAHTERAAN HEWAN SELAMA 60 HARI (Prevalence of Behavioural Changes in Male Local Dog (Canis familiaris) Caged Based on Animal Welfare Principles for 60 Days) - Nofri Alfi; Teuku Reza Ferasyi; Erdiansyah Rahmi; Mulyadi Adam; Idawati Nasution; Ismail Ismail (Jurnal Medika Veterinaria, 2015)
The aim of this research was to determine the prevalence of behavioral changes of male local dog caged based on animal welfare principles. A total of three male local dogs was used as the experiment object. Dog behavior was observed using focal animal sampling method. Dogs were caged for 60 days, provided with sufficient food and water ad libitum. The dogs were identified based on their color and body size. Their behavior were observed three times each days in the morning, midday, and afternoon with 3 periods: period I (day 1 to day 20), period II (day 21 to day 40), and period III (day 41 to day 60). The observation was carried out for 60 days with allocation time was 30 minutes/ each observations. The result obtained indicated that the prevalence of behavior in dogs during the first period was dominated by sitting and sleeping. In addition, they were showed the behavior of running, walking, playing, sniffing, and eating. During this period, they were also expressed of stress behavior, such as barking, digging, backward/hiding, biting, and climbing. In the second and third periods of observation, the behaviors of sitting and sleeping are increased while behaviors of stress are reduced. Based on this results, it can be concluded that local dogs indicate stress behavior during the first 20 days caged, then they become more calm during the following days when animal welfare principle is fulfilled.Key words: local dog, dog behavior, animal welfare